Михайло Зубрицький – діяльний член Наукового товариства імені Шевченка у Львові - Глушко, М. (Народна творчість та етнологія, 2020)
У статті йдеться про наукову діяльність Михайла Зубрицького – відомого українського археографа, історика, етнографа та фольклориста. З’ясовано історію його вступу до Наукового товариства імені Шевченка у Львові (1896), обрання дійсним членом Товариства (1904) і членом Етнографічної комісії (1905), причетність Івана Франка та Михайла Грушевського до цих неординарних для священика подій. Докладно розглянуто співпрацю М. Зубрицького з різними науково-дослідними підрозділами першої української наукової установи. Встановлено: проживаючи у віддаленому від Львова гірському селі Мшанець, науковець-парох особисто відвідав сім засідань Історично-філософської секції, по одному разу засідання Археографічної і Статистичної комісій і двічі – загальні збори Товариства. На засіданнях Історично-філософської секції обговорили та рекомендували до друку 20 основних джерелознавчих, історичних та етнографічних досліджень уродженця Бойківщини, які він підготував упродовж 1897–1911 років. Членам цього науково-дослідного підрозділу сам М. Зубрицький представив лише 4 статті, а решту його розвідок подали інші вчені: І. Франко – 5, М. Грушевський – 6, Володимир Гнатюк – 4, Стефан Томашівський – 1. Тексти підготовлених археографічних та етнографічних досліджень автор часто доповнював цікавими фактами навіть під час їх верстання у друкарні. М. Зубрицький причетний також до проведення першої комплексної (етнографічно-антропологічної) експедиції українських народознавців (1904). Результати праці її учасників (І. Франка, Федора Вовка, Зенона Кузелі) вплинули на подальші етнографічні зацікавлення вченого. Зокрема, після завершення цієї наукової мандрівки дослідник активно вивчав народну матеріальну культуру бойків – житло, одяг і взуття. Із 1904 року він систематично поповнював етнографічні колекції різних музеїв Європи (Етнографічного музею у Відні (Австрія), Етнографічного музею у Базелі (Швейцарія), Музею НТШ у Львові) цікавими пам’ятками традиційно-побутової культури і народного мистецтва населення північно-західної частини Бойківщини. The article is dedicated to the analyses of the scientific work of Mykhailo Zubrytskyi, a famous Ukrainian archaeographer, historian, ethnographer, and folklorist. The history of his entry in the Shevchenko Scientific Society in Lviv (1896), his election as a full member of the Society (1904) and a member of the Ethnographic Commission (1905), and Ivan Franko and Mykhailo Hrushevskyi participation in these extraordinary as for the priest events have been revealed. M. Zubrytskyi's collaboration with various research subdivisions of the first Ukrainian scientific institution has been considered in detail. It has been established that he has lived in a mountain village of Mshanets remote from Lviv. Now it belongs to the Staryi Sambir district of the Lviv region. The scholar-pastor personally has attended seven meetings of the Historical and Philosophical Section, once a meeting of the Archaeographic and Statistical Commissions, and twice the General Meeting of the Society. During the meetings of the Historical and Philosophical Section 20 major source, historical and ethnographic studies of M. Zubrytskyi as a native of Boikivschyna, prepared by him during 1897–1911, have been discussed and recommended for printing. Mykhailo Zubrytskyi has proposed only 4 of his own articles to the members of this research subdivision. The rest of his studies have been prepared by the other scholars: I. Franko – 5, M. Hrushevskyi – 6, Volodymyr Hnatiuk – 4, Stefan Tomashivskyi – 1. The author has often completed the texts of archaeographic and ethnographic research by interesting facts, even in the process of their imposing in the printing house. M. Zubrytskyi has also been concerned with the realization of the first comprehensive (ethnographic-anthropological) field expedition of Ukrainian ethnographers in 1904. The results of the work of its participants (Ivan Franko, Fedir Vovk, and Zenon Kuzelia) have influenced the further ethnographic interests of the scientist. In particular, the researcher has studied actively the national material culture of Boiky – housing, clothing, and footwear – after the completion of this scientific journey. Since 1904 he has replenished systematically the ethnographic collections of various museums in Europe (Ethnographic Museum in Vienna (Austria), Ethnographic Museum in Basel (Switzerland), Shevchenko Scientific Society Museum in Lviv) with interesting monuments of traditional and everyday culture of the north-western part of Boikivshchyna.